Isolation, structure, characterization and cytotoxicity assessment of alkaloids from Ficus fistulosa var. tengerenisis (Miq.) Kuntze - Al-Khdhairawi, A. A. Q. (2018)
The alkaloidal content from the leaves of a local Malaysian plant, Ficus fistulosa var. tengerensis (Miq.) Kuntze was investigated following a preliminary screening which revealed the presence of alkaloids in the plant. However, the bark material was devoid of alkaloids and was thus not investigated. The leaves of F. fistulosa var. tengerensis were collected in large scale, dried, ground and extracted with 95% ethanol. Acid-base treatment of the ethanolic crude extract followed by numerous chromatographic processes resulted in the isolation of five alkaloids. The pure alkaloids were subjected to spectroscopic analysis (NMR, UV, IR, X-ray and ECD) for structure elucidation. Of the five alkaloids isolated, two were novel alkaloids, namely, (±)-tengerensine (1) and (±)-tengechlorenine (2). (±)-Tengerensine (1), was isolated as a pair of racemic enantiomers and they represent a pair of rare unsymmetrical cyclobutane dimers and the first dimeric benzopyrroloisoquinoline alkaloids to be discovered. (±)-Tengechlorenine (2), was isolated as a scalemic mixture with a slight excess of the dextrorotatory enantiomer. (±)-Tengechlorenine (2) represents the first chlorinated phenanthroindolizidine alkaloid to be isolated. In addition to the two new alkaloids, three known alkaloids were also isolated and characterized, viz., ()-fistulosine (3) a benzopyrroloisoquinoline alkaloid, (S)-(+)-antofine (4) a phenanthroindolizidine alkaloid, and (R)-()-secoantofine (5) a septicine-type alkaloid. In vitro antiproliferation assay was carried out on alkaloids (±)-1, (+)-1, (-)-1 and 3 on a small panel of breast cancer and normal cell lines, including MCF-7, MDA-MB-231 and MDA-MB-468 (human breast adenocarcinoma cells), and MCF-10A (non-tumorigenic breast epithelial cell breast epithelial cells). (+)-Tengerensine 1 was found to display a selective cytotoxic effect against MDA-MB-468 cells (IC50 7.4 uM), while (±)-1, (-)-1 and 3 were found to be generally ineffective against all the cell lines tested.